Enhancing School Adjustment in Secondary School Students through Artificial Intelligence - Huma Naz (Journal of Research in Education and Pedagogy, 2025)
School Adjustment is a critical factor in the overall development and well-being of secondary school students, influencing their academic performance, social integration, and emotional health. The integration of artificial intelligence in education offers an innovative solution to support students during this transitional phase. This paper explores how artificial intelligence correlates with school adjustment. This study was conducted on secondary school students of CBSE, ICSE, and U.P board students. Here, to examine the school adjustment of secondary school students from CBSE, ICSE, and U.P. boards, and to explore the relationship between the use of artificial intelligence and their school adjustment across these educational boards. In this study, the researcher used self-constructed tools (Artificial Intelligence Scale and School Adjustment Scale). A total of 300 secondary school students’ data was collected using the psychological tools. This paper indicates that students have different levels of school adjustment due to boards. In CBSE and ICSE boards students school adjustment is higher than as compared to U.P board students because in U.P board school does not get effective learning resources. This study found a moderate correlation between artificial intelligence and school adjustment. This study highlights the transformative potential of artificial intelligence in fostering a supportive and inclusive school environment for secondary school students.